Strategic Action for the Development of Social Impact Businesses: Evidence from Brazilian Amazon - Bravim, Jhordano Malacarne; Segatto, Andréa Paula; Justen, Gelciomar Simão; Carvalho, Ana Carolina Vilela (Archives of Business Research, 2023)
This research sought to understand how governments of the nine states that make up the Brazilian Amazon plan to act strategically to develop social impact businesses. From the analysis of the Multi-Year Plans 2020-2023 and through qualitative research with content analysis, we identified that all state governments of the Brazilian Amazon consider in some way the relationship with social impact businesses as a strategy for the development of various themes. 47 passages identified are related to 14 thematic areas (economy; social development; work, employment, and income; science, technology, and innovation; family agriculture; integrated development; agribusiness; regional development; health; planning, budget, and management; fishing; partnerships; industrial development; and, culture, sports, and leisure) and 5 organizational formats (solidarity economy enterprises; collective entrepreneurship; solidary economy; associations; and cooperatives) that have collectivism and solidarity in common. A relational model of the strategic action of the state governments of the Brazilian Amazon through social impact businesses indicates the predictability of strategic initiatives for the development of this kind of business.